GREAT BRITAIN: LANGUAGE AND LITERATURE - Kozyrev, A.L.; Nazmutdinova, S.S.; Popov, D.S.; Chugaeva, T.N.; Shpak, N.E. (Perm Federal Research Centre Journal, 2016)
The article looks into the issues of the English language and literature as an expression of the national mentality. Aspects of the history and development of British literature are considered. The literary process of the different parts of UK - England, Scotland and Ireland is discussed. Contribution of the outstanding writers and poets into the development of British and world culture is estimated. Practical assignments in English are offered to extend the knowledge of British culture and literature.